Scale‐Up of a Crystallizer for Production of Nano‐Sized Energetic Materials. Issue 7 (16th June 2016) - Jung, Wooyoung; Park, Junyong; Lee, Woojin; Lee, Jaecheol; Koo, Keekahb; Oh, Min
Abstract: The outstanding sensitivity of high‐energetic materials such as cyclotrimethylenetrinitramine (RDX) and octahydro‐1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocane (HMX) has prompted efforts by researchers in the production of less sensitive explosives by crystallization without compromising performance. One such endeavor is crystal‐size reduction to nano‐scales. The optimum operating conditions for producing nano‐sized RDX were experimentally determined. Based on these results, computational fluid dynamics modeling and simulations were executed for scale‐up purposes and identification of the influence of fluid dynamics, mixing, and heat transfer on crystal growth and production rate on commercial scales. As a result, a commercial plant was designed and operation data from the commercial crystallizers were compared with data obtained from scale‐up tasks. Abstract : Cyclotrimethylenetrinitramine (RDX) is an extremely sensitive high‐energetic explosive. For safety issues, experiments were conducted for the production of insensitive nano‐sized RDX. The effects of hydrodynamic parameters on RDX size under different operating conditions were analyzed by computational fluid dynamic simulations. As a result, a commercial crystallizer could be designed.